Analyse de la legitimation de la transition et de la Nouvelle République Démocratique du Congo - Apala Pen’Apala, Christophe Lutundula (Afrika Focus, 1997)
The aim of this article is to assess the institutional order and the legitimating of the A.F.D.L. government in order to propose some political adjustments which could consolidate the current transition process. To evaluate the institutional order of the present Congolese Republic, it is necessary to examine the A.F.D.L. Declaration of Assumption of Power and the Constitutional Decree Law number 3. The Declaration of Assumption of Power has important politcal as well as legal consequences. Politically it stipulates that only the A.F.D.L. is entitled to govern the Congolese state. Legally the Declaration creates a dangerous vacuum. It merely installs a president and a government, and it suspends allformer constitutional laws. The Constitutional Decree Law number 3 was proclaimed to restore the constitutional order and to organise the execution of power. The institutional order established by this Decree Law has two major consequences. It legitimates the otherwise ’unlawful’ appointment of some members of the new government, and it establishes a very strong presidential regime without constitutional separation of powers. The political legitimation of the A.F.D.L. government implies the existence of popular support and international recognition of that government. A strong ground for the overwhelming popular support for the A.F.D.L. is based on Congolese history, especially on the political legacy of Patrice Lumumba, although it has to be said that the legitimating of the present regime is also based on the inadequacy of all former regimes. In addition, it should be noted that the National Sovereign Conference also derived its legitimation from its task to end the existing chaos. Nevertheless, however strong that legitimating may be, now that the old regime is overthrown, chaos still exists and will provoke socio-economic claims. That is the reason why legitimation has to be based on new goals which exceed a simple change of rulers. Four conclusions can be drawn from this analysis. First of all, the Decree Law is regarded as a very temporary law and consequently it has only established a few pieces of an institutional order. This makes it necessary to create a real republican constitution. Secondly, the existing institutional order risks slipping away into a strong presidential regime. Another consequence is that the present institutional order is open to dictatorship, although it is unlikely that such an evolution can be consolidated by way of social consensus. The challenge will consist in organising a system of political pluralism which can develop into an efficient instrument of development. In the end, good governance implies the social and economic well- being as well as the political development of a nation. Finally, the legitimation of the A.F.D.L. is fragile. Therefore it has to be based on a political program which makes national reconciliation possible. Such a reconciliation should include a consensus between the A.F.D.L. and the National Sovereign Conference on the options for a new social contract. KEY WORDS : Congo, constitution, Kabila, politics